2021
DOI: 10.1016/j.sjbs.2021.04.073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of new sulfur-containing fertilizers on performance of wheat yield

Abstract: Wheat is the main cereal crop in Kazakhstan and fertilizers play an important role in enhancing harvest growth. In this study, the impact of new sulfur-containing fertilizers on the growth and yield of wheat was evaluated, and the resistance of varieties to Puccinia triticina Erikss was also investigated. (also known as Puccinia recondite Rob. ex Desm.) for recommendations in agriculture. The study was conducted from 2017 to 2020 in a nursery and greenhouse. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Pandey’s [ 42 ] results for oat, in correlation with our findings, showed that the yield from sulphur application, in addition to the balanced use of NPK nutrients, outperformed the yield with NPK fertilizers alone, by 7.1%. Kurmanbayeva et al [ 43 ] in a greenhouse setting and Klikocka et al [ 44 ] in a field experiment also observed similar increases (3.58%) in grain yield with sulphur fertilization in wheat.…”
Section: Discussionmentioning
confidence: 61%
“…Pandey’s [ 42 ] results for oat, in correlation with our findings, showed that the yield from sulphur application, in addition to the balanced use of NPK nutrients, outperformed the yield with NPK fertilizers alone, by 7.1%. Kurmanbayeva et al [ 43 ] in a greenhouse setting and Klikocka et al [ 44 ] in a field experiment also observed similar increases (3.58%) in grain yield with sulphur fertilization in wheat.…”
Section: Discussionmentioning
confidence: 61%
“…The effect of S amendment on plant defense response had contributed to similar evidence. As such, the soil amendment of S-containing fertilizer on wheat varieties increased resistance against brown rust and improved the overall productivity 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Вчені [14] вважають, що ефективним заходом обмеження поширення розвитку бурої листкової іржі є створення стійких сортів. Виявлено сорт пшениці, що має два гени стійкості Lr28 і Lr68.…”
Section: уманський національний університет садівництваunclassified